Investigating the applicability of molecular dynamics simulation for estimating the wettability of sandstone hydrocarbon formations - Khosravi, V. (American Chemical Society, 2020)
One of the techniques to increase oil recovery from hydrocarbon reservoirs is the injection of low salinity water. It is shown that the injection of low salinity water changes the wettability of the rock. However, there are argumentative debates concerning low salinity water effect on changing the wettability of the oil/brine/rock system in the oil reservoirs. In this regard, molecular dynamics simulation (MDS) as a tool to simulate the phenomena at the molecular level has been used for more than a decade. In this study, the Zisman plot (presented by KRUSS Company) was simulated through MDS, and then, contact angle experiments for n-decane interactions on the Bentheimer substrate in the presence of different concentrations of sodium ions were conducted. MDS was then used to simulate experiments and understand the wettability trend based on free-energy calculations. Hereafter, a new model was developed in this study to correlate free energies with contact angles. The developed model predicted the experimental results with high accuracy (R2 â¼0.98). A direct relation was observed between free energy and water contact angle. In contrast, an inverse relation was noticed between the ion concentration and the contact angle such that an increase in the ion concentration resulted in a decrease in the contact angle and vice versa. In other terms, increasing brine ionic concentrations in the presence of n-decane is linked to a decrease in free energies and an increase in the wetting state of a sandstone. The comparison between the developed model's predicted contact angles and experimental observations showed a maximum deviation of 14.32, which is in satisfactory agreement to conclude that MDS can be used as a valuable and economical tool to understand the wettability alteration process. Copyright Â© 2020 American Chemical Society.